Pendampingan Kelompok Tani "Pintoe Rimba" Desa Naga Umbang, Aceh Besar melalui Optimalisasi Pengolahan Minyak Herbal Tradisional - Ruka Yulia; sholihati sholihati; Kiman Siregar (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
“Pintoe Rimba" farmer group of Naga Umbang, Lhoknga Subdistrict, Aceh Besar makes traditional herbal oils with conventional method and simple packaging. The quality of traditional herbal oil produced has not been standardized. Its production is not carried out every day due to the lack of equipment and knowledge. The mentoring of "Pintoe Rimba" farmer group conducted by the team for optimizing the process of making traditional herbal oils using distillation equipment as effort to improve skills, quality standards, sustainable production and economy in the farmer group. The stages of this mentoring include: 1) Socialization; 2) Counseling about entrepreneurs for increasing economic; 3) Training in packaging and labeling; and 4) Optimizing the making of herbal oil by using distillation equipment. The outcomes of this mentoring are a) The partners have knowledge about improving the entrepreneurial economy for their family, b) The partners are able to package and label the traditional herbal oil product using sealer, c) The partners are able to use distillation equipment that can increase traditional herbal oil production; and d) The partners can produce herbal oil with better quality standards.